Biomass fuel smoke exposure was associated with adverse cardiac remodeling and left ventricular dysfunction in Peru. (16th January 2017) - Burroughs Peña, M. S.; Velazquez, E. J.; Rivera, J. D.; Alenezi, F.; Wong, C.; Grigsby, M.; Davila‐Roman, V. G.; Gilman, R. H.; Miranda, J. J.; Checkley, W.
Abstract: While household air pollution from biomass fuel combustion has been linked to cardiovascular disease, the effects on cardiac structure and function have not been well described. We sought to determine the association between biomass fuel smoke exposure and cardiac structure and function by transthoracic echocardiography. We identified a random sample of urban and rural residents living in the high‐altitude region of Puno, Peru. Daily biomass fuel use was self‐reported. Participants underwent transthoracic echocardiography. Multivariable linear regression was used to examine the relationship of biomass fuel use with echocardiographic measures of cardiac structure and function, adjusting for age, sex, height, body mass index, diabetes, physical activity, and tobacco use. One hundred and eighty‐seven participants (80 biomass fuel users and 107 non‐users) were included in this analysis (mean age 59 years, 58% women). After adjustment, daily exposure to biomass fuel smoke was associated with increased left ventricular internal diastolic diameter ( P =.004), left atrial diameter ( P =.03), left atrial area (four‐chamber) ( P =.004) and (two‐chamber) ( P =.03), septal E ′ ( P =.006), and lateral E ′ ( P =.04). Exposure to biomass fuel smoke was also associated with worse global longitudinal strain in the two‐chamber view ( P =.01). Daily biomass fuel use was associated with increased left ventricular size and decreased left ventricular systolic function by global longitudinal strain.